Conversion to IUI versus continuance with IVF in low responder patients: A systematic review. (August 2018) - Fujii, Dennis T.; Quesnell, Jodi L.; Heitmann, Ryan J.
Abstract: Poor response to ovarian hyper-stimulation can be difficult to predict prior to stimulation even when factoring in patient age and ovarian reserve testing. When faced with the situation of poor response, patients and providers have the difficult decision to proceed with oocyte retrieval, convert to intrauterine insemination (IUI), or cancel the cycle. Although this is not an uncommon scenario, there is little data available to assist with the counseling of these patients. We performed a systematic review of published studies comparing clinical pregnancy and live births between those patients continuing with in-vitro fertilization (IVF) and those converting to IUI. PubMed and Ovid were searched for all retrospective and randomized studies using the Keywords ' in-vitro fertilization', 'intrauterine insemination', 'poor responders', 'clinical pregnancy' and 'live birth rates'. A total of seven retrospective studies and one randomized control trial were reviewed. When evaluating poor responders as a group, six studies reported higher overall clinical pregnancy rates and five studies reported overall increased live birth rates with continuance of IVF. When stratified by the number of follicles produced, continuance of IVF demonstrated higher clinical pregnancy and live birth rates with ≥ 2 follicles. When only one follicle developed there were no significant differences in clinical pregnancy or live birth rates between the two groups. In patients undergoing IVF with ≤4 follicles, continuance with IVF may lead to higher clinical pregnancy and live birth compared to conversion to IUI except in patients with monofollicular development, although additional randomized controlled trials are needed to confirm these findings.